Teachers' beliefs about creative students' characteristics: A qualitative study. (March 2019) - Gralewski, Jacek
Abstract: The aim of the present study was to examine teachers' beliefs about creative students' characteristics and the possible gender differences in this respect. The study took the form of in-depth individual interviews conducted with 15 Polish secondary school teachers. We found that the interviewed teachers described a creative student mainly in terms of his or her personality traits relevant from the perspective of creativity, cognitive predisposition towards creativity, and motivation. Moreover, a creative student was described in terms of characteristics relating to artistic abilities, intelligence, and functioning at school. The interviewed teachers described a creative boy differently than they described a creative girl. As opposed to a creative girl, a creative boy was described as impulsive, independent, rule-breaking, courageous, willing to take risks, capable of defending his opinion, self-confident, individualistic, spontaneous, go-getting, and quickly getting down to action, whereas a creative girl was described mainly as diligent, conscientious, systematic, persistent, calm, acting according to plan, consistent, and well-behaved, but also as submissive and conformist, obeying all kinds of rules and regulations, avoiding risk, and acting according to instructions or a plan. The causes of these differences are discussed in the context of creativity types and styles, gender stereotypes, and different educational expectations for students of different genders.